Mimicking the Crude Oil and Heavy Fuel Oil (HFO) Demulsification Process in Power Plants for Preparing a New Demulsifiers - Hamdy, Faris Moayed Ahmed; Raouf, Abdullatif Mohammed; Esmael, Israa Abdulsatar; Thuaban, Laith Hamza; Ibraheem, Nadia Fakhry; Yas, Hiba Mahmoud; Ali, Maher Talib; Salman, Zakya Salah Al Deen; Jabir, Najim Abd Alhusain; Yousif, Tamadhir Neama (Journal of Petroleum Research and Studies, 2020)
Water–in–oil emulsions are a big challenge in the production and processing of crude oil due to its bad influence on the fundamental and practical aspects of industrial facilities. Researches for decades gave this phenomena a great deal in the planning to construct power plants, refineries, oil companies and other industrial facilities that uses crude oil as a raw material. In order to overcome the disadvantages and hazards of water–in–oil emulsions researchers used chemical, electrical, thermal and mechanical methods individually or in combination. The chemical method has gained the main interest due to its ease of use and economic feasibility. Demulsifiers have been used extensively to solve the problem of water in oil emulsions. The choice of using the right combination of chemicals had been reached after studying many factors such as cost and safety. This research addresses many fundamental and practical aspects regarding demulsifiers and oil demulsification aiming to find the best selection of chemicals that can be used to treat crude oil before using, refining or transporting it. The crude oil in this research had been demulsified and tested by the spectroil test method while the bottle test method had not been used to mimic the demulsification process used in power plant. The work was carried out using two types of oil, crude oil (containing 7 ppm Na and K salts concentration) and heavy fuel oil HFO (containing 12 ppm Na and K salts concentration). The crude oil samples were taken from Al – Hilla 2 power plant while the HFO samples were taken from South Baghdad 2 power plant. The results showed that the water miscible chemicals and chemicals with sufficient solubility that used as a demulsifiers like the acrylic derivatives gave the best demulsification when using more wash water percentage. While the combination of water miscible chemicals and chemicals with sufficient solubility and oil soluble chemicals gave the best results in treating heavy fuel oil while using less wash water percentage.